Efek mediasi makna hidup pada hubungan antara GRIT dan kepuasan hidup pada mahasiswa - Djaling, Krisna Wardhana; Purba, Debora Eflina (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2019)
The current study aimed at examining the relationship between grit and life satisfaction through meaning in life. Data were taken using online survey from university students in Depok city (N = 505). Variables were measured using The Grit Scale, Meaning in Life Questionnaire (MLQ), and Satisfaction With Life Scale (SWLS). Data were analyzed using simple mediation model on Hayes PROCESS macro on SPSS program. Results showed that grit was positively and significantly related with life satisfaction and meaning in life, respectively, and meaning in life positively and significantly related with life satisfaction. Lastly, meaning in life partially mediated the relationship between grit and life satisfaction.